Type A dissection and fistula to right atrium after aortic valve replacement. (May 2016) - Kang, Ming-Yuan; Hsieh, Shih-Rong
A 73-year-old man with a history of severe aortic regurgitation underwent aortic valve replacement with a bioprosthesis. Nine years later, he presented with heart failure and was diagnosed with chronic type A dissection and severe aortic stenosis. During surgery, a fistula from the ascending aortic aneurysm to the right atrium was found incidentally. Replacement of the aortic valve and ascending aorta were performed successfully. The fistula was closed with sutures. The patient was discharged uneventfully on postoperative day 16.